The detection of latent fingermarks on porous surfaces using amino acid sensitive reagents: A review - Jelly, R.; Patton, E.; Lennard, C.; Lewis, Simon; Lim, K. (Elsevier BV, 2009)
The introduction of ninhydrin treatment as a chemical technique for the visualisation of latentfingermarkson porous surfaces revolutionised approaches to forensic fingermark examination. Since then, a range ofamino acid sensitive reagents has been developed and such compounds are in widespread use by lawenforcement agencies worldwide. This paper reviews the development and use of these reagents for thedetection of latent fingermarks on porous surfaces. A brief overview is provided, including an historicalbackground, forensic significance, and a general approach to the development of latent fingermarks onporous surfaces. This is followed by a discussion of specific amino acid sensitive treatments.